2021
DOI: 10.1111/ppc.12790
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' spiritual caregiving status: Comparison of Western and Central Anatolia regions of Turkey

Abstract: The aim of this study was to determine the status of spiritual caregiving education in nursing students belonging to two different state universities in Turkey.Design and Methods: The descriptive, cross-sectional study was completed with 326 students.Findings: Turkey's western regions in mean scale scores of students (147.27 ± 19.40) in central Anatolia (140.83 ± 18.82) was higher than the students and the difference was statistically significant. A statistically significant difference was found between the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A study in Turkey by Karaman et al ( 2022 ) showed there are even differences between the development levels and cultures within the regions of that country where the study was conducted at two universities in very different regions. Students in the Western region scored significantly higher on their spiritual caregiving than students in the Central Anatolia region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in Turkey by Karaman et al ( 2022 ) showed there are even differences between the development levels and cultures within the regions of that country where the study was conducted at two universities in very different regions. Students in the Western region scored significantly higher on their spiritual caregiving than students in the Central Anatolia region.…”
Section: Discussionmentioning
confidence: 99%
“…In other regions of the country, the Anatolian culture that is heavily influenced by religious beliefs is more prevalent. Moreover, a special elective palliative care course was available in the Western university and not in the Anatolian one (Karaman et al, 2022 ). Further investigation is needed to better understand spiritual care in Turkey (Daghan, 2018 ) as well as other countries around the world, and to identify the elements responsible for differences in the scores of spiritual care competencies within nursing/midwifery among various cultures and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation